2021
DOI: 10.1038/s42003-021-02511-5
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils dominate in opsonic phagocytosis of P. falciparum blood-stage merozoites and protect against febrile malaria

Abstract: Antibody-mediated opsonic phagocytosis (OP) of Plasmodium falciparum blood-stage merozoites has been associated with protection against malaria. However, the precise contribution of different peripheral blood phagocytes in the OP mechanism remains unknown. Here, we developed an in vitro OP assay using peripheral blood leukocytes that allowed us to quantify the contribution of each phagocytic cell type in the OP of merozoites. We found that CD14 + +CD16− monocytes were the dominant phagocytic cells at very low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 38 publications
5
43
0
Order By: Relevance
“…Further, antibodies promoted activation of NK cells, which occurs via engagement of FcγRIIIa, which may also contribute to immunity against sporozoites [18, 23]. Our data, and other published data [23, 43] suggest that neutrophils are substantially more active in phagocytosis than monocytes and are much more abundant than monocytes in blood (45–70% and 2–10% of peripheral blood white blood cells, respectively). This suggests neutrophils may play a more prominent role in clearance of sporozoites in blood.…”
Section: Discussionsupporting
confidence: 76%
“…Further, antibodies promoted activation of NK cells, which occurs via engagement of FcγRIIIa, which may also contribute to immunity against sporozoites [18, 23]. Our data, and other published data [23, 43] suggest that neutrophils are substantially more active in phagocytosis than monocytes and are much more abundant than monocytes in blood (45–70% and 2–10% of peripheral blood white blood cells, respectively). This suggests neutrophils may play a more prominent role in clearance of sporozoites in blood.…”
Section: Discussionsupporting
confidence: 76%
“…Although IgG levels were comparable between individuals with asymptomatic and symptomatic parasitemia, plasma from individuals in the younger group with asymptomatic parasitemia significantly inhibited parasite invasion in vitro compared to plasma from those with symptomatic malaria, in younger age group. Given that the parasitemia levels between asymptomatic and symptomatic individuals in this group were similar, this data may reflect the fact that antibodies control iRBCs through several mechanisms apart from invasion blocking such as facilitating opsonic phagocytosis by phagocytes by neutrophils (62). If such other metrics are similar between the 2 groups then invasion blocking effects may be hidden by the cumulative action of circulating antibodies.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, merozoite phagocytosis was shown in vitro to be enhanced in the presence of immune sera or when interferon‐γ (IFN‐γ), tumour necrosis factor‐α (TNF‐α) or granulocyte‐monocyte colony‐stimulating factor (GM‐CSF) was added 13,47,48 . Recently, it was demonstrated that at low levels of specific antibodies, merozoites are mainly phagocytosed by monocytes through FcγRIIA, whereas at high antibody levels, neutrophils are more effective through synergistic action of FcγRIIA and FcγRIIIB 49 …”
Section: Role Of Neutrophils In the Defence Against Plasmodium Parasitesmentioning
confidence: 99%
“…13,47,48 Recently, it was demonstrated that at low levels of specific antibodies, merozoites are mainly phagocytosed by monocytes through FcγRIIA, whereas at high antibody levels, neutrophils are more effective through synergistic action of FcγRIIA and FcγRIIIB. 49 This may suggest that monocytes are mainly responsible for the phagocytosis of parasites in non-immune patients, while neutrophils appear more important in immune patients. As an illustration, the presence of trophozoites, gametocytes, schizonts and haemozoin within the neutrophils and a large number of neutrophils with phagocytosed merozoites were described in a recent clinical case report.…”
Section: Role Of Neutrophil S In the Defen Ce Ag Ain S T Pl A Smodium...mentioning
confidence: 99%